Revisiting the diversity and distribution of the ophiuroids (Echinodermata: Ophiuroidea) from Peru - Fernández, Rebeca Granja; Hooker, Yuri (Zootaxa, 2020)
While the Ophiuroidea of Peruvian waters have long been studied, there exists inconsistencies regarding taxonomy and spatial distribution records. Based on literature review and museum records, we provide an updated checklist of the ophiuroids accompanied by the first geographical distribution analysis. Peruvian waters host 36 species of Ophiuroidea (three doubtful), yet 15 previous records of species are considered invalid for the area. We recorded five new records of species for Peru: Amphiodia oerstedi, Diopederma daniana, Ophiocomella alexandri, Ophiolepis crassa, and Ophiophthalmus normani. Peruvian maritime area is divided into four areas: The Tropical Eastern Pacific area where 16 species of ophiuroids occur, the Transition Zone with 13 species, the Warm Temperate Southeastern Pacific with nine species, and the Deep Zone with 14 species. We found significant differences in species composition among areas (except among the Eastern Pacific and the Transitional Zone), and each of them is represented by particular species. According to the rarefaction curve, the inventory of ophiuroids for the country is not yet complete; therefore, we suggest performing more expeditions along the Peruvian waters focusing mainly on the deep zones which remain relatively unexplored to date.